PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASIONAL PADA GURU SMA NEGERI DI KABUPATEN TEMANGGUNG - Murtuty Ningsih, 11.5202.0054 (Students Journal of Economic and Management, 2013)
This study is aimed to examining and analyzing the influence of the transformasional leadership and job satisfaction toward the teacherâs performance through the mediation of Â the organizational commitment to teachers in Temanggung state senior highÂ schools. The population ofÂ this study includesÂ all the permanent teachers of the state senior high school in Temanggung the number of the respondents 139. The data of this study is collected through questionaire with the scale of 7 point likert. The analysis of this data is in the form of the description of the responden and the description of the variable. The method used to examinedÂ the data includes the validity test with factor analysis and the reliability test using the Cronbachâs Alpha formula, the model of double regression analysis is examined Â by using coefficient determination and F test, signification test to prove the truth of the hipotesa, as well as the mediation test. The result of the study shows that The Transformasioanal Leadership has noÂ influence to the organizational commitment, Â The Job Satisfaction influence positivelyÂ the organizational commitment, Â The Transformasional Leadership has positive influenceÂ on the teacherâs performance, Â The Job Satisfaction also has positive influence on the techerâs performance,Â The Organizational Commitment has positive influence on the teacherâs performance as well.Â The result of this research is indicated that the influence of transformasional leadership and job satisfaction toward teacher performance not mediated by organizational commitment. Key words : Transformasional LeadershipÂ ,Â Job Satisfaction,Â OrganizationalCommitment,Â and Teacherâs Performance